Energy Audit with Innovative Technology Management for Resourcing the Clean Energy and Sustainability in India - Sivapriya, C; Preetha, S; Rajendran, V (International Journal of Engineering and Technology, 2018)
Energy is an essential input to the overall development of the economy. It provides light and fuel to millions of households, industry, agriculture, commerce all service sectors and so on. Since energy is a critical component, development of conventional and non-conventional forms of energy for meeting the growing demand of the society at reasonable price and quality is the responsibility of the government. Energy Audit is an important and vital tool in the management of energy both at industry and nation level. It is required for improvising the efficient management practices in energy production, utilization and distribution with better technology and to thereby conserve for future growth and development. With the growing importance for industrial sectors in the countryâ€™s development and increasing energy consumptions, it has become essential and necessity to opt for more optimization methods in the consumption of energy. A saving of 15 to 30% can be done by optimal usage of energy at home. Energy conservation and safety is the topmost priority in todayâ€™s world to have a consistent growth, increase in production and to protect our environment. Energy audit and its management is instrumental to cope with the variation in the cost of energy, to identify the appropriate mixes of energy, to improvise the energy conservative equipment and technologies.Â Along with innovative technology for energy consumptions we also require innovative methods in the management of energy audit to help the country with efficient energy management system, reduce cost and save energy for future requirements. To study and understand the need for Energy audit with innovative technology management in India. To analyze its importance for resourcing clean energy and sustainability in India.